The construction of the transhumance territory of the gerÊs-xurÉs: Vernacular heritage identification, analysis and characterization - Carlos E. Barroso (2018)
In order to ensure survival, the rural populations of the Gerês-Xurés mountain range transboundary region developed, over centuries, a very specific system of vertical transhumance. Focus on making the most out of their natural landscape harsh conditions, human intervention shaped the territory, and gave birth to the existent and very authentic vernacular heritage, that has in the corbelled dome building technologies one of its most characteristic identity features. In the pursuit of fertile land, villages were scattered in small and compact settlements, built at lower altitude and occupied all year long. The surrounding mountains slopes were turned into farming terraces, and the high-altitude plateaus were for livestock and farming, thru temporary settlements built in corbelled dome structures. These vital points were interconnect by a dense network of paths and masonry walls. Although the resemblance between most of the region permanent settlements, the temporary nuclei, due to each mountain particular features, show a large morphological and functional diversity, from complex structures, like the brandas or the brandas e inverneiras system, to very simple pasture areas, like the currais. Understanding the high potential of this endanger vernacular heritage is a key point for its preservation, as well as its recognition by the scientific community and society in general. A previous study aimed at the brandas morphological and constructive characterization was presented at the Rehabend 2016. This follow-up study is focus on, in a first level, the identification and characterization of the general system main features, and, in a second level, the evaluation of this vernacular heritage main preservation threats. The research, based on case studies analysed thru fieldwork surveys, geometrical and constructive, and literature support, allowed to identify the main morphological and typological features related to the heritage elements that take part in this occupation system, and are discussed in this paper.